Knowledge and behavior of diabetes mellitus patients who follow the Ramadan fast - Nugroho, Fajar Ari; Wilujeng, Catur Saptaning; Handayani, Dian; Kusumastuty, Inggita; Mohd Yusof, Barakatun Nisak (Brawijaya University, 2022)
The rapid development of the prevalence of diabetes mellitus (DM) has been shown in low and middle-economic countries. For a Muslim with diabetes, the obligation to fast during the month of Ramadan will certainly be a challenge. Recent research by some researchers from several countries states that Muslims with diabetes commonly continue to fast regardless of the risks faced, and the need for providing knowledge to reduce or avoid complications. This study was an analytical descriptive study that examines the general description of knowledge and behavior of diabetic patients who observe the Ramadan fasting. This research was a pilot survey research where there has never been similar research conducted in Indonesia. The target population is diabetic patients who fast during Ramadan, both type 1 and type 2. The sample was determined using the purposive sampling method. Data collection is done using Google forms for one month of Ramadan from June to July 2021. The results of this study indicate that DM patients already know how to fast while maintaining their condition. Although the results do not show a significant relationship between DM indicators and independent variables from patients (p > 0.001), these results can still illustrate that patients still need assistance to maximize DM control during the fast.